(untitled) - Hyden, Janet S. (Mason, OH, 2006)
Learn by doing with Communicating for Success! Not only will you learn how to communicate effectively in the workplace, but you’ll also discover how to apply these communication skills to your real life. Practice exercises, projects, teamwork activities, and career connections help you develop effective communication skills. Studying is easy with the Data CD that includes additional practice and extension of in-text materials.
Keywords: Business communication,Communication,Commercial correspondence; Study and teaching,Study and teaching,Study and teaching